Effectiveness, immunogenicity, and safety of the quadrivalent HPV vaccine in women and men aged 27–45 years. Issue 5 (30th November 2022) - Maldonado, Ivette; Plata, Manuel; Gonzalez, Mauricio; Correa, Alfonso; Nossa, Claudia; Giuliano, Anna R.; Joura, Elmar A.; Ferenczy, Alex; Ronnett, Brigitte M.; Stoler, Mark H.; Jin Zhou, Hao; Joshi, Amita; et al.
ABSTRACT: Among women aged 27–45 years, the quadrivalent human papillomavirus (qHPV; HPV6/11/16/18) vaccine was generally well tolerated, efficacious, and immunogenic in the placebo-controlled FUTURE III study (NCT00090220; n = 3253). The qHPV vaccine was also generally well tolerated and highly immunogenic in men aged 27–45 years who participated in the single-cohort mid-adult male (MAM) study (NCT01432574; n = 150). Here, we report results of a long-term follow up (LTFU) extension of FUTURE III with up to 10 years follow-up. To understand the relevance of the mid-adult women LTFU study in the context of mid-adult men vaccination, we report results from post-hoc, cross-study immunogenicity analyses conducted to compare immunogenicity (geometric mean titers; GMTs) at 1-month post-qHPV vaccine dose 3 in women and men aged 27–45 years versus women and men aged 16–26 years from prior efficacy studies. The qHPV vaccine demonstrated durable protection against the combined endpoint of HPV6/11/16/18-related high-grade cervical dysplasia and genital warts up to 10 years (median 8.9) post-dose 3 and sustained HPV6/11/16/18 antibody responses through approximately 10 years in women aged 27–45 years. Efficacy of qHPV vaccine in men aged 27–45 years was inferred based on the cross-study analysis of qHPV vaccine immunogenicity demonstrating non-inferior HPV6/11/16/18 antibody responses in men aged 27–45 years versus 16–26 years. In conclusion, durable effectiveness of the qHPV vaccine was demonstrated in women 27–45 years of age, and vaccine efficacy was inferred in men 27–45 years of age based on the serological results.